Modulation of Physical and Thermal Properties in Wild Banana (Musa balbisiana Colla) Seed Powder by Moisture Variations - Murlidhar Meghwal; Chitra Lekhwar; Yogesh Kumar; Vivek Kumar; Rajat Suhag; Pramod K. Prabhakar (International Journal of Food Science)
Engineering and flow properties of banana seed powder as a function of moisture content are important for processing, handling, packaging, and transport processes. The bulk density, tapped density, and porosity increased from 377.37 to 427.36 kg m-3, 622.08 to 746.33 kg m-3, and 38.99-43.74%, respectively, within the increasing moisture content range. The Hausner ratio (Hr) and Carr’s compressibility index (CI) significantly (p<0.05) increased with an increase in moisture content (6.16-19.56% db) of banana seed powder, whereas HR fell in the range of 1.4-2.0, indicating cohesive characteristics of banana seed powder. The angle of repose, angle of spatula, and angle of fall exhibited a linear increase, ranging from 40.6° to 49°, 33.4° to 39.4°, and 35.6° to 42.6°, respectively, with increasing moisture content. The static coefficient of friction was found to be highest for aluminium and glass surfaces and least for stainless steel. The water activity and swelling power of banana seed powder showed a significant increase, while the solubility and oil absorption capacity exhibited a significant decrease within the range of increasing moisture content. The thermal characteristics of wild banana seed powder, such as thermal conductivity (0.16 to 0.20 Wm−1 K−1) and volumetric specific heat (0.58 to 0.99 MJm−3 K−1), demonstrated an increasing trend as the moisture content increased. However, the thermal diffusivity showed a decrease from 0.31 to 0.19 (×10−6 m2s−1) with the increase in moisture content.